Secondary School Teachers’ Perspectives on Reading Literacy: Insights and Challenges - Usenik, Janja; Puncer, Mojca (Bralni vzori 2, 2025)
The aim of this chapter was to gain insight into the understanding and experience of reading literacy among secondary school teachers, and to identify good practices and barriers to its development in an era of digital change. Data for the analysis were collected through a focus group method involving secondary school teachers from different subject areas. In promoting reading literacy, teachers emphasised the importance of cross-curricular integration, acting as reading role models, and using authentic texts that are close to the students. They highlighted the low motivation of young people to read, their limited vocabulary and the impact of digital technologies that encourage surface reading. They also pointed to the lack of systemic support and adequate professional training. The findings point to the need for a holistic development of reading and digital literacy, more professional support and adjustments in school policies to better respond to the challenges of modern reading in a technologically saturated environment.